Sequence analysis of 5' regulatory regions of the Machado-Joseph Disease gene (ATXN3) - Bettencourt, C. (2012)
Machado–Joseph disease (MJD) is a late-onset autosomal dominant neurodegenerative disorder, which is caused by a coding (CAG)n expansion in the ATXN3 gene (14q32.1). The number of CAG repeats in the expanded alleles accounts only for 50 to 75 % of onset variance, the remaining variation being dependent on other factors. Differential allelic expression of ATXN3 could contribute to the explanation of different ages at onset in patients displaying similar CAG repeat sizes. Variation in 5′ regulatory regions of the ATXN3 gene may have the potential to influence expression levels and, ultimately, modulate the MJD phenotype. The main goal of this work was to analyze the extent of sequence variation upstream of the ATXN3 start codon. A fragment containing the core promoter and the 5′ untranslated region (UTR) was sequenced and analyzed in 186 patients and 59 controls (490 chromosomes). In the core promoter, no polymorphisms were observed. In the 5′ UTR, only one SNP (rs3814834) was found, but no improvements on the explanation of onset variance were observed, when adding its allelic state in a linear model. Accordingly, in silico analysis predicted that this SNP lays in a nonconserved position for CMYB binding. Therefore, no functional effect could be predicted for this variant.